Survey on available bandwidth estimation in ad hoc network - WU Da-peng; WU Mu-qing; ZHEN Yan (Tongxin xuebao)
With analysis of the difference between bandwidth estimation scheme in wired network and wireless network,the available bandwidth in mobile ad hoc network is defined. The factors which infect the available bandwidth including frame collision probability,backoff time and channel utilization are analyzed; meanwhile,the methods of measurement and estimation are also given; finally,the application and research trend of available bandwidth estimation is pointed out.